Experimental Study on Dynamic Mechanical Properties and Energy Evolution Characteristics of Limestone Specimens Subjected to High Temperature. (9th June 2020) - Ping, Qi; Zhang, Chuanliang; Su, Haipeng; Zhang, Hao
Abstract : To study the effect of high temperature on the dynamic mechanical properties and energy evolution characteristic of limestone specimens, the basic physical parameters of limestone specimens that cool naturally after experiencing high temperatures of room temperature (25°C), 200°C, 400°C, and 600°C were tested. In addition, compression tests with 6 impact loading conditions were conducted using SHPB device. The changes of basic physical properties of limestone before and after temperature were analyzed, and the relationship among dynamic characteristic parameters, energy evolution characteristics, and temperature was discussed. Test results indicated that, with the increase of temperature, the surface color of specimen changed from gray-black to gray-white, and its volume increased, while the mass, density, and P-wave velocity of specimen decreased. The dynamic compressive stress-strain curve of limestone specimens after different high-temperature effects could be divided into three stages: elasticity stage, yield stage, and failure stage. Failure mode of specimen was in the form of spalling axial splitting, and the degree of fragmentation increased with the increase of the temperature and incident energy. With the increase of the temperature, the reflection energy, the absorption energy, the dynamic compressive strength, and dynamic elastic modulus of rock decreased, while its transmission energy, the dynamic peak strain, and strain rate increased. The dynamic compressive strength, dynamic elastic modulus, dynamic strain, and strain rate of limestone specimens all increased with the increase of incident energy, showing a quadratic function relationship.